Carotenoid-based skin ornaments reflect foraging propensity in a seabird, Sula leucogaster. (26th September 2018) - Michael, Nathan P.; Torres, Roxana; Welch, Andreanna J.; Adams, Josh; Bonillas-Monge, Mario Erandi; Felis, Jonathan; Lopez-Marquez, Laura; Martínez-Flores, Alejandro; Wiley, Anne E.
Abstract : Carotenoid-based ornaments are common signalling features in animals. It has long been proposed that such ornaments communicate information about foraging abilities to potential mates. However, evidence linking foraging with ornamentation is largely missing from unmanipulated, free-ranging populations. To investigate this relationship, we studied a coastal population of brown booby ( Sula leucogaster brewsteri ), a seabird with a carotenoid-based gular skin ornament. δ 13 C values from both feathers and blood plasma were negatively correlated with male gular colour, indicating birds that consumed more pelagic prey in offshore locations had more ornamented skin than those that fed on nearshore, benthic prey. This relationship was supported by our GPS tracking results, which revealed longer, more offshore foraging trips among highly ornamented males. Our data show that brown booby ornaments are honest indicators of foraging propensity; a link consistent with the rarity hypothesis and potentially driven by the concentration of carotenoids found in phytoplankton versus benthic algae. Carotenoid-based ornaments may reflect foraging tendencies in animals such as coastal predators that use food webs with distinct carotenoid profiles.